The Influence of Risk Attitude towards the Entrepreneurial Intention - Filmina , Azzahra; Mayangsari, Lidia (KnE Social Sciences, 2020)
Currently, Indonesia has a goal to increase the number of entrepreneurs for about 20,000 new enterprises in 2019. This number is increasing every year, which indicate the urgency of the government to emerge entrepreneurs within the society (Kompas, 2018). Many factors can form an entrepreneur. They can be encouraged from family background, hobbies, needs, and also through an educational system. A different method of teaching and treatment will drive different entrepreneurial results. Several studies show that entrepreneurs behave differently. Entrepreneurs create and manage their business to achieve their business goals. It makes the entrepreneur is having the willingness to give resource on it, such as pays the material used in the business, rent a place, and higher employee. It also makes them have more willingness to take the risk along the entrepreneurial activity (Paun, 2013). Therefore, the researcher wants to discover the relationship between entrepreneurial intention and risk attitude. This research uses a quantitative approach in order to explore the study and use a questionnaire as the tools. The result was analyzed using the single linear regression method with SPSS software. Single linear regression is a statistical method used to explain the relationship between dependent and independent variables. The independent variables in this research would be Risk Attitude, and the independent variable would be Entrepreneurial Intention. From that, the research hypotheses would be entrepreneurs risk attitude significantly affected entrepreneurial intention; the higher risk attitude of a person will increase their entrepreneurial intention. Keywords: risk attitude, entrepreneurial intention, entrepreneurs